OTOMATIS SPRAY DESINFEKTAN KANDANG AYAM DENGAN ANDROID BERBASIS ARDUINO UNO - Mohammad Bahrul Ulum; Dwi Hadidjaja Rasjid Saputra (Research Parks Publishing LLC, 2020)
Technology plays a very important role in human life. Many devices and applications are created to facilitate human work. In the world of chicken farming many problems are found both in terms of objects and their management. In chicken farms, problems often arise about the decline in the quality of livestock due to disease attacks. Diseases in chicken farms arise due to poor chicken coop conditions and lack of attention from the management. To maintain the condition of the chicken coop remains sterile from disease attacks, then spraying disinfectant chemicals. Disinfectant chemicals are classified as dangerous when exposed to the human body directly. Automatic chicken cage disinfectant spray with Android-based arduino UNO aims to simplify and provide a sense of security when spraying disinfectant for farmers. The process of spraying disinfectant can be done remotely using an Android smart phone application and Arduino Uno microcontroller hardware with Bluetooth communication. HC-05 bluetooth module as a communication medium between Android smart phone with arduino Uno, diarfaghma 12 vdc pump, 80 psi as spray disinfectant while disinfectant spray drive uses 5 vdc motor. Automatic chicken cage disinfectant spray can be done at a maximum distance of 10 meters.